International Mobility of Labor in the Informal Sector - Axinte, Gheorghe (Journal of Advanced Research in Economics and International Business; Vol 1 No 1 (2013): JAREIB Volume I Issue 1 Summer 2013, 2013)
Increasing levels of international migration is countered by progressively restrictive immigration barriers, which leads to a substantial number of people who use irregular channels of migration and foreign employment. Growing proportion of migrants which moves without entry clearance is combined with those who resort the procedures of asylum without meeting the conditions of refugee status or other forms of protection. Migration- asylum combination affects a number of concerns, such as the actual management of borders, identifying legitimate claims for asylum from this mix flows, trafficker’s network discovery etc. The potential to find a job is a key factor that encouraging illegal immigration into the European Union (EU).